The impact of short-term comprehensive treatment on cardiovascular-kidney-metabolic syndrome and its components in patients with type 2 diabetes - Gong, Li; Yang, Ruirui; Cui, Huanhuan; Zhao, Jing; Liu, Jing; Lv, Xiaoshaung; Ding, Jing (Frontiers in Endocrinology, 2025)
ObjectiveThe purpose of this study was to evaluate the interaction of risk factors and effects of short-term comprehensive treatment on the staging and components of cardiovascular-kidney-metabolic (CKM) syndrome in patients with type 2 diabetes mellitus (T2DM).MethodsThe study included 541 patients with T2DM who received comprehensive treatment from November 2023 to December 2024. The study analyzed the baseline clinical characteristics and CKM stage. Of these, 204 patients completed a six-month follow-up, forming a real-world observational study. This study evaluated changes in CKM stage and 10-year cardiovascular disease (CVD) risk scores in patients with CKM stages 2 and 3 after six months of intensive treatment. A multivariate logistic regression was used to analyze the factors influencing the 10-year CVD risk.ResultsAmong 541 adult patients with T2DM, 83.2% were in CKM stage 2, 11.1% in CKM stage 3, and 5.7% in CKM stage 4. Of the 204 patients who completed a six-month comprehensive intervention, 177 (43.2%) were in CKM stage 2 and 18 (7.3%) were in CKM stage 3, with a significant improvement in CKM stage 3 (4.1%) after the intervention. The 10-year CVD risk score decreased from 8.3% to 5.8% before and after the intervention (P<0.05). Multivariate logistic regression analysis revealed that for every 1% decrease in HbA1C, the 10-year CVD risk decreased by 71.5%[OR = 1.715,95%CI(1.386-2.123. For every 1mmol/L decrease in TC, the 10-year CVD risk decreased by 70%[OR = 1.700,95%CI(1.070-2.701. For every 1mmHg decrease in systolic blood pressure, the 10-year CVD risk decreased by 5.9%[OR = 1.059,95%CI(1.027-1.090. For every 1mmol/l increase in HDL-C, the 10-year CVD risk decreased by 4.9%[OR = 0.049,95%CI(0.006-0.442)].ConclusionShort-term comprehensive treatment can improve the staging of CKM syndrome in T2DM patients and reduce the 10-year CVD risk score; the decrease of SBP, TC and HbA1c and the increase of HDL-C under comprehensive treatment are protective factors for the improvement of the 10-year CVD risk score.